(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
أجريت الدراسة في مزرعة الحرية في (حريصون- بانياس) خلال عامي 2003-2004 على شجيرات كيوي صنف Hayward بعمر 4 سنوات عند بدء التجربة مكاثرة بالعقل ومزروعة بالطريقة المربعة ( 3×3 م). الغرض من إجراء التجربة دراسة تأثير كميات الماء المضاف ومواعيده في إنتاجية وجودة ثمار شجيرات الكيوي باستخدام طريقتين للري: § الري بالتنقيط Drip irrigation والري الرذاذي من تحت تاج الشجيرة irrigation under foliage sprinkler شملت الدراسة 9 معاملات لكل طريقة وبثلاثة مكررات لكل معاملة, ويمكن تلخيص النتائج: 1-تفوق الري الرذاذي على الري بالتنقيط في كل من: - متوسط إنتاج الشجيرة( 8.6 كغ عند الري الرذاذي و7.3 كغ عند الري بالتنقيط ). - النسبة المئوية للمادة الجافة في الثمرة (18.04 % عند الري الرذاذي و17.6 % عند الري بالتنقيط). - النسبة المئوية للسكريات الأحادية في الثمرة (7.64% عند الري الرذاذي و5.8 % عند الري بالتنقيط). - محتوى الثمرة من فيتامين C (70.6 مغ/100 غ وزن طازج عند الري الرذاذي و60.8 مغ/100 عند الري بالتنقيط). 2-تفوق الري بالتنقيط على الري الرذاذي في: - النسبة المئوية للمواد الصلبة الذائبة في الثمرة (13.6 %عند الري بالتنقيط و13.5% عند الري الرذاذي). - النسبة المئوية للأحماض العضوية في الثمرة (1.1 % عند الري بالتنقيط و1% عند الري الرذاذي). 3-تفوق الكمية 100 لتر للشجيرة كل 3 أيام (78% من السعة الحقلية ) على باقي المعاملات في : - متوسط إنتاج الشجيرة ( 13.3 كغم عند الري الرذاذي و10 كغم عند الري بالتنقيط ). 4-تفوق الكمية 100 لتر للشجيرة كل 4 أيام (75 % من السعة الحقلية ) على باقي المعاملات حيث بلغت أعلى قيمة لمتوسط وزن الثمرة (109 غ عند الري الرذاذي و98 غ عند الري بالتنقيط ). وكذلك النسبة المئوية للأحماض العضوية في الثمرة كانت الأعلى عند هذه الكمية ( 1.1 % عند الري الرذاذي و1.22% عند الري بالتنقيط ). 5-تفوق الكمية 100 لتر للشجيرة كل 5 أيام (72% من السعة الحقلية) على باقي المعاملات في: -أعلى نسبة للسكريات الأحادية في الثمرة 8.13 % عند الري الرذاذي و6.52 % عند الري بالتنقيط ). -أعلى نسبة للفيتامين C في الثمرة ( 77مغ \100 غ وزن طازج عند الري الرذاذي و72 مغ 100غ وزن طازج عند الري بالتنقيط . This study was conducted in Al Horeyaih farm (Hriasoon-Banyas) during 2003-2004 growing season on four years old Kiwi trees (Variety Hayward) planted in distance of 3 by 3 meters to study the effect of quantity and times of irrigation on yield and Fruit quality. Two methods of irrigation were used. Drip irrigation and under foliage sprinkler irrigation. Nine treatments were used for each irrigation method with three replicates for each treatment. The results showed that: 1- Under foliage sprinkler irrigation proved to be better than Drip irrigation in the following: • The average of tree yield (8.6 kg in Mini sprinkler irrigation and 7.3 kg in Drip irrigation). • The percentage of fruit dry maters (18.04% in under foliage sprinkler irrigation and 17.6% in Drip irrigation). • The percentage of mono saccharid in the fruit (7.94% in under foliage sprinkler irrigation and 5.8 % in Drip irrigation). • Vitamin C in the fruit (70.6 mg/100g fresh weight in under foliage sprinkler irrigation and 60.8 mg/100g fresh weight in Drip irrigation). 2- Drip irrigation proved to be better than under foliage sprinkler irrigation in the following: • Percentage of total soluble solid materials (13.6% in Drip irrigation and 13.5% in Mini sprinkler irrigation). • Percentage of fruit organic acids (1.1% in Drip irrigation and 1% in under foliage sprinkler irrigation). 3-Irrigation with 100 litter water/tree every three days (78% field capacity) proved to be better than other treatments in the following: • Average of tree yield (13.3 kg in under foliage sprinkler irrigation and 10 kg in Drip irrigation). 4-Irrigation with 100 litter water/tree every four days (75% field capacity) proved to be better than other treatments in the following: • Highest fruit average weight (109 g in under foliage sprinkler irrigation and 98 g in Drip irrigation). • Highest percentage of fruit organic acids (1.1% in Mini sprinkler irrigation and1.22% in Drip irrigation). 5-Irrigation with 100 litter water/tree every five days (72% field capacity) proved to be better than other treatments in the following: • Highest percentage of mono saccharid in the fruit (8.13% in under foliage sprinkler irrigation and 6.52 % in Drip irrigation). • Highest content of vitamin C in the fruit (77 mg/100g fresh weight in under foliage sprinkler irrigation and 72 mg/100g fresh weight in Drip irrigation).